The relationship between perceived quality association and purchase intention to patronage Islamic brand restaurants - Mohd Yusof, Yuslina Liza; Wan Jusoh, Wan Jamaliah; Maulan, Suharni (2016)
Malaysia has gained the reputation as one of the most developed Muslim countries and a Haven for Halal food. Due to increasing trade, tourism and globalization, demand for Halal food which is considered to be high quality, hygienic and delicious is growing both in Malaysia as well as internationally. Therefore, the purpose of this study is to investigate the relationship between perceived quality association and purchase intention to patronage Islamic brand restaurants among Muslims in Malaysia, particularly in the Klang Valley. Using a self-reporting questionnaire, data from 531 respondents were obtained and analysed using SEM-PLS. The results showed that perceived quality association has significant and positive influences on intention to patronage Islamic brand restaurants. Therefore, it is important for Islamic brand restaurants to concentrate on service personnel aspect and food taste in formulating their marketing strategies to sustain their competitive advantage. These insights could be used to overcome the challenges of purchase intention of Islamic brand restaurants.